Analysis of the Role of Decent Living Standards and Knowledge on Human Development Index Growth - Ramadhani Hamzah; Mutiara Shifa; Musdirwan Musdirwan; Indra Ismayudi Tanjung; Liasulistia Ningsih; Saut Maruli Tua Pandiangan (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
The purpose of this study is to analyze the role of decent living standards and knowledge on human development index growth in Indonesia. This research analysis uses qualitative analysis. Data collection in this study uses secondary data taken from Badan Pusat Statistik Indonesia. The study results show that Indonesia's human development index grew faster in 2024, reaching 75.02, an increase of 0.63 points (0.85 percent) compared to 74.39 in 2023. Decent living standards dimension which measures real per capita expenditure per year, adjusted for Indonesians, increased by 2.89 percent annually from 2020 to 2024. In 2020, real per capita expenditure, adjusted for Indonesians, reached Rp11,013,000, increasing to Rp12,341,000 in 2024. Indicators forming the knowledge dimension, including expected years of schooling and average years of schooling, continued to increase. During the 2020 to 2024 period, Indonesia's expected years of schooling increased by an average of 0.44 percent per year, while average years of schooling increased by 1.07 percent per year.